ADOLESCENTS AND PARENTAL DIVORCE (STUDY OF ADOLESCENT RESILIENCE AFTER PARENTS DIVORCE EACH OTHER IN PAMPANGAN HAMLET, A'BULOSIBATANGVILLAGE, MARUSU SUB-DISTRICT) - Surianti, Surianti; Ismail, Ashari; Jusnawati, Jusnawati (Social Landscape Journal, 2025)
This study aims to determine (1) what factors affect the resilience of adolescents after parents divorce each other in Pampangan Hamlet, A'bulosibatang Village, Marusu Subdistrict, (2) Forms of resilience of adolescents after parents divorce each other in Pampangan Hamlet, A'bulosibatang Village, Marusu Subdistrict. This type of research is qualitative research with the determination of research subjects through purposive sampling technique. Data collection techniques, namely observation, interviews and documentation used to obtain concrete data related to the problems that are the subject of this study. This data was analyzed using a phenomenological approach. The results of this study show and know that: (1) Factors that influence adolescents after parents divorce each other, namely (a) Individual factors include the potential or abilities that exist within adolescents such as individuals trying to understand and understand the situation they are experiencing, the formation of independence to be responsible for themselves and their families, generate their own income at a young age and be able to build communication or interaction with the surrounding environment. (b) Family factors, namely the relationship between individuals and families is well established so as to get financial and emotional support to individuals. (c) Community factors, namely adolescents' involvement in extracurricular activities at school and active in social environmental activities. (2) Forms of adolescent resilience, namely (a) Compensation, the formation of adolescent economic independence through daily work (b) Protection, namely avoiding conflict and building relationships or social interactions well, especially with positive relationships between family members (c) Challenge, is an individual mindset where adolescents are able to help reduce family burdens such as working at a young age or managing personal expenses wisely. They are also able to maintain focus on goals for their future despite the family's unstable financial condition.